Data innovations on protests in the United States. (January 2023) - Dorff, Cassy; Adcox, Grace; Konet, Amanda
For decades, the United States has been generally excluded from cross-national quantitative datasets on the study of collective action and political resistance. More recently, however, new data collection efforts are on the rise. These projects specifically focus on gathering granular level information about street protests and mobilizations in the United States. In this article, we conduct a rigorous exploratory data analysis of three contemporary protest datasets. These data collect information about the when, where and how of contentious politics in the United States. Our thorough data review first summarizes the key similarities and differences across the datasets. Next, we review the regional, temporal and methodological strengths and weaknesses of each dataset both individually and in contrast to one another. Last, we examine potential research applications of these data by demonstrating what these data reveal about the risks of protesting in these types of events. We conclude by offering recommendations for data use and future data collection strategies for the study of collective action.